2006
DOI: 10.3748/wjg.v12.i17.2737
|View full text |Cite
|
Sign up to set email alerts
|

Splenic vasculopathy in portal hypertension patients

Abstract: Type III procollagen and collagen might be important extra-cellular matrix resulting in neointimal formation and vascular remodeling in the pathogenesis of portal hypertensive vasculopathy. The pathological changes in splenic arteries and veins exist in portal hypertension patients. There might be an interaction between portal hypertension, splanchnic hyperdynamic circulation and splanchnic vasculopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…This study showed that the reduction in spleen volume was significant 4–40 months after OLTX ( p < 0.01); however, many recipients still had splenomegaly after OLTX. This may be due to chronic morphological changes such as splenic vasculopathy and an increase in small venous sinuses in the red pulp due to chronic congestion [11, 12]. Yanaga [3] observed reduction in the spleen volume with a mean of 23% in 8 patients who underwent OLTX.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that the reduction in spleen volume was significant 4–40 months after OLTX ( p < 0.01); however, many recipients still had splenomegaly after OLTX. This may be due to chronic morphological changes such as splenic vasculopathy and an increase in small venous sinuses in the red pulp due to chronic congestion [11, 12]. Yanaga [3] observed reduction in the spleen volume with a mean of 23% in 8 patients who underwent OLTX.…”
Section: Discussionmentioning
confidence: 99%
“…Smooth muscle cells, randomly located in media, have a different size and morphology, and the content of separating them collagen fibers, as well as the extracellular matrix, increases significantly, causing the “collagenization” of the vascular wall, thickening, and rigidity[53]. The splenic vein expanding and its intima and media thickening is due to high content of collagen fibers, hypertrophy, and hyperplasia of smooth muscle cells[54].…”
Section: The Systemic and Splanchnic Adaptive Response Of Vascular Bementioning
confidence: 99%
“…Внутренняя эластическая мембрана расслаивается, причем входящие в ее состав (как и локализованные в медиальном слое) эластические волокна разрушаются. Беспорядочно рас-положенные в медиальном слое гладкомышечные клетки имеют различный размер и морфологию, а содержание разделяющих их коллагеновых волокон так же, как и вне-клеточного матрикса, значительно увеличивается, вызы-вая «коллагенизацию» сосудистой стенки, ее утолщение и ригидность [50]. Селезеночная вена расширяется, ее ин-тима и медиальный слой за счет повышенного содержа-ния коллагеновых волокон, гипертрофии и гиперплазии гладкомышечных клеток утолщаются [51].…”
Section: актуальные вопросы физиологииunclassified